Sound Loop Superoptimization for Google Native Client - Churchill, Berkeley; Sharma, Rahul; Bastein, JF; Aiken, Alex (ASPLOS 17, 2017)
Software fault isolation (SFI) is an important technique for the construction of secure operating systems, web browsers, and other extensible software. We demonstrate that superoptimization can dramatically improve the performance of Google Native Client, a SFI system that ships inside the Google Chrome Browser. Key to our results are new techniques for superoptimization of loops: we propose a new architecture for superoptimization tools that incorporates both a fully sound verification technique to ensure correctness and a bounded verification technique to guide the search to optimized code. In our evaluation we optimize 13 libc string functions, formally verify the correctness of the optimizations and report a median and average speedup of 25% over the libraries shipped by Google.